Self-efficacy in first-time mothers: a comparison of younger and older mothers - Eaton, Michelle Marie (Kansas State University, 2007)
When compared to adult mothers, adolescent mothers are more prone to parenting challenges (Whitman et al., 2001). Age is considered influential on a mother’s belief in her ability to successfully organize and execute her parenting plan (Bandura, 1999). The purpose of this study was to examine potential predictors of self-efficacy (determinant of parenting) among first-time mothers applying Belsky’s (1984) parenting framework. Maternal age, maternal depression, available social support and infant temperament were all considered to be potential predictors of maternal self-efficacy. A sample of first-time mothers (N = 115) with no other children in the home with an infant between the ages of four and six months was recruited from local alternative high schools, home and center child care facilities, and various other social services agencies and programs that typically serve new mothers. Participants self-reported on the above variables by completing a survey measuring self-efficacy as well as the hypothesized predictors. Responses were analyzed using group mean comparisons between 3 age groups: mothers 19 years and under (23%); mothers 20-26 years of age (29%); and mothers 26 years of age and older (48%). No significant differences in self-efficacy, perceived infant temperament, social support were found between age groups. Age differences in maternal depression fell just below significance. Maternal income level was significantly (and negatively) correlated with maternal depression, therefore was controlled for in additional analyses. Annual income, depression, and self efficacy were significantly correlated to perceived infant temperament. Mothers with lower incomes, who perceived less social support, who reported higher levels of depression, or had lower levels of self-efficacy were found to rate their infants as more temperamentally difficult. Regression analyses demonstrated that level of perceived social support significantly predicted maternal self-efficacy levels across all age groups. Additionally, infant temperament and maternal depression levels predicted self-efficacy. These findings provide evidence to support the importance of equal accessibility and affordability of social support for all new mothers to assist with the positive transition to parenthood.
Keywords: First-Time Mothers; Self-Efficacy in Mothers; Maternal Self-Efficacy; Transition to Motherhood; Health Sciences, Human Development (0758)